Comparison of saccharification and fermentation of steam exploded rice straw and rice husk. Issue 1 (December 2016) - Wood, Ian; Cao, Huong-Giang; Tran, Long; Cook, Nicola; Ryden, Peter; Wilson, David; Moates, Graham; Collins, Samuel; Elliston, Adam; Waldron, Keith
Abstract Background Rice cultivation produces two waste streams, straw and husk, which could be exploited more effectively. Chemical pretreatment studies using rice residues have largely focussed on straw exploitation alone, and often at low substrate concentrations. Moreover, it is currently not known how rice husk, the more recalcitrant residue, responds to steam explosion without the addition of chemicals. Results The aim of this study has been to systematically compare the effects of steam explosion severity on the enzymatic saccharification and simultaneous saccharification and fermentation of rice straw and husk produced from a variety widely grown in Vietnam (Oryza sativa, cv. KhangDan18). Rice straw and husk were steam exploded (180–230 °C for 10 min) into hot water and washed to remove fermentation inhibitors. In both cases, pretreatment at 210 °C and above removed most of the noncellulosic sugars. Prolonged saccharification at high cellulase doses showed that rice straw could be saccharified most effectively after steam explosion at 210 °C for 10 min. In contrast, rice husk required more severe pretreatment conditions (220 °C for 10 min), and achieved a much lower yield (75 %), even at optimal conditions. Rice husk also required a higher cellulase dose for optimal saccharification (10 instead of 6 FPU/g DM). Hemicellulase addition failed to improve saccharification. Small pilot scale saccharification at 20 % (w/v) substrate loading in a 10 L high torque bioreactor resulted in similarly high glucose yields for straw (reaching 9 % w/v), but much less for husk. Simultaneous saccharification and fermentation under optimal pretreatment and saccharification conditions showed similar trends, but the ethanol yield from the rice husk was less than 40 % of the theoretical yield. Conclusions Despite having similar carbohydrate compositions, pretreated rice husk is much less amenable to saccharification than pretreated rice straw. This is likely to attenuate its use as a biorefinery feedstock unless improvements can be made either in the feedstock through breeding and/or modern biotechnology, or in the pretreatment through the employment of improved or alternative technologies. Physiological differences in the overall chemistry or structure may provide clues to the nature of lignocellulosic recalcitrance.